Determination of allowable time for decision making in Collision Avoidance Systems in Free Flight Environment - Харченко, В.П.; Кукуш, О.Г.; Васильєв, В.М. (Proceedings of National Aviation University (archive), 2004)
A method of a sequential time evaluation of choice of variant and decision making to avoid predicted dangerous approach of the aircraft at implementation of Free Flight concept in air traffic management is presented. Expressions for an evaluation of boundary instants by using the spline method are derived. Interval estimation is given by calculation of a confidence time interval.